Mapping and assessment of land cover change and ecological stability: a case of three transects in Slovakia - Jana Vojteková; Matej Vojtek; Martin Boltižiar; František Petrovič; Matej Masný; Bohuslava Gregorová (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of this paper is to analyze and assess the land cover change in three transects in Slovakia by applying the coefficient of ecological stability and the coefficient of anthropogenic impact in four different time horizons (1950, 1990, 2000, and 2020). Based on the specific natural and socio-economic factors influencing landscape formation and change, we chose three transects from the territory of Slovakia as study areas. The study areas are located in western Slovakia (transect called Záhorie: Rudava – Buková), central Slovakia (transect called Turiec: Martin – Moškovec), and eastern Slovakia (transect called Poloniny: Stakčín – Ruské).